Design and Optimization of Fibrous Filter Media Using Lifetime Multipass Simulations. Issue 5 (6th April 2018) - Azimian, Mehdi; Kühnle, Christopher; Wiegmann, Andreas
Abstract: The goal of this study was to optimize fibrous filter media by increasing the dust holding capacity (DHC) while maintaining the β ratio and initial pressure drop of the filter media. The key was the use of microstructure models to optimize the filter media. The microstructure of three different variations of a filter media for oil filtration was modeled by using the FiberGeo module of the GeoDict® software package. It was found that by optimizing the fiber volume distribution over the height of the filter media, higher DHC values could be achieved while keeping the pressure drop considerably low. This confirms the hypothesis that the macroscopic properties of the filter element can be improved by modifying the microstructure of the filter media. Abstract : The macroscopic properties of a filter can be optimized by modification and optimization of the microstructure of the filter media. Filtration simulations on three different models of an oil filter media were run using GeoDict®. The results showed that by changing the distribution of the fine fiber type through the model height, the dust holding capacity of the filter media changed as well.